ABDUL AL-HAMĪD JAUDĀH AL-SAHĀR WĀ MANHĀJŪHŪ FĪ AL-FIKR AL-ISLAMĪ - Maimanah Binti Samsuri (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2020)
Abstract Islamic Literature books have been among the modern literary arts being read by many people who want to know more about Islam, but most of these books have one or two issues. Though, there were many well-known Islamic writers like Najib al-Kilani, Abu al-Hasan al-Nadawi, and their likes. The aim of this study was to examine the work of Abdul Hamid Jaudat Sahar, by looking at his life history, literary works, and critical writings in aspects of Islamic thought. The study has implemented a library method and analytical approach in looking at his literary and non-literary works. The study also concluded that the thought and methods used in Abdul Hamid Jawdat Sahar's writing were more of focusing on Islamic writings and religious stories that are more suitable for children. Key word: Abdul Hamid Jaudat Sahar, Islamic Thought, Methodology